Metabolomic changes and biological activities during the lacto-fermentation of jackfruit juice using Lactobacillus casei ATCC334 - Muhialdin, Belal J.; Meor Hussin, Anis Shobirin; Kadum, Hana; Abdul Hamid, Azizah; Jaafar, Ahmad Haniff (Academic Press, 2021)
This study aimed to evaluate the potential for developing probiotic beverage using jackfruit juice via lacto-fermentation with Lactobacillus casei ATCC334. The viable cells count was significantly (p < 0.05) increased from 6 Log10 CFU mL−1 to 8.176 Log10 CFU mL−1 after fermentation for 24 h at 37 °C and decreased to 7.672 Log10 CFU mL−1 after 3 weeks at 8 °C. The antioxidant activity increased to 305.204 mM Fe(II)/mg and DDPH IC50 15.65 mg/mL. Strong antimicrobial activity obsereved towards Escherichia coli 0157:H7 (95%), Salmonella enterica serovar Typhimurium (98%) and Staphylococcus aureus (95%). Sugars content significantly (p < 0.05) reduced, while lactic acid and GABA significantly (p < 0.05) increased. No significant (p ≥ 0.05) differences were observed for the overall sensory properties for fermented and non-fermented jackfruit juice. The results of this first study showed the high potential to develop probiotic beverage with broad range of biological activities via lacto-fermentation of the jackfruit juice.